2011
DOI: 10.1007/s11746-011-1945-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Oil Content and Fatty Acid Composition in Cottonseed Kernel Powder Using Near Infrared Reflectance Spectroscopy

Abstract: Oil content and fatty acid composition in 444 ground cottonseed kernel samples were analyzed using near infrared reflectance spectroscopy (NIRS). Calibration equations were developed for oil and fatty acid contents with the modified partial least squares (MPLS) regression method. The correlations between NIRS and reference values in external validation were in agreement with the predictions in calibration. Each equation was assessed based on the relative prediction determinant for external validation (RPD v ).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
1
26
1
1
Order By: Relevance
“…Spectral coverage was in the 1,100-2,500 nm wavelength band. Elfadl et al (2010) with safflower (R 2 = 0.90) and Quampah et al (2012) with cotton (R 2 = 0.99) were other authors who have reported interesting results working in the spectral band of wavelengths above 1,100 nm. Velasco et al (1999b), in similar work with seeds from the Brassicaceae germplasm, developed a model for the prediction of oil content having an R 2 equal to 0.97.…”
Section: Also Inmentioning
confidence: 94%
See 4 more Smart Citations
“…Spectral coverage was in the 1,100-2,500 nm wavelength band. Elfadl et al (2010) with safflower (R 2 = 0.90) and Quampah et al (2012) with cotton (R 2 = 0.99) were other authors who have reported interesting results working in the spectral band of wavelengths above 1,100 nm. Velasco et al (1999b), in similar work with seeds from the Brassicaceae germplasm, developed a model for the prediction of oil content having an R 2 equal to 0.97.…”
Section: Also Inmentioning
confidence: 94%
“…This assumes that the use of many LVs, more than nine, increases the error and lowers the predictive robustness of the VIS-NIR model. Quampah et al (2012), Liu et al (2009), Sivakesava and Irudayaraj (2002) and Swierenga et al (1999) consider that over-adjusted models can be avoided by selecting the optimal number of LVs using the minimum RMSECV, with a relatively high R 2 . .…”
Section: Effect Of Pre-treatment Of the Spectral Datamentioning
confidence: 99%
See 3 more Smart Citations